Education regarding the Importance of Adjusting Study Habits when Implementing Face-to-Face Learning for Students in the Covid-19 Transition Period - Sultan Nazmi Chairul Islam; Rina Maryanti (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The research conducted by the author aims to observe and educate more broadly on the impact of the transition from online to offline learning, the readiness of students to face offline learning, and the way students adapt their study habits during the Covid 19 transition period in the education sector, especially in the transition from online learning to online learning. offline. The research method used in this journal is a qualitative descriptive analysis method. Analysis of survey data is processed by collecting data, filtering data, presenting data, and simplifying data. Then the data from the research analysis are summarized in concepts and classified according to categories and poured into descriptive form then the conclusion is drawn. The results of the education that has been provided can be seen in increasing students' insight into online and offline learning. This is evidenced by the increasing results of the tests that have been carried out by the respondents. This is due to the increased insight of the respondents as a result of the education that has been given. The impact of this research is that the respondents who are students feel that offline learning is necessary because it affects the level of understanding of learning. Then, the students felt that they were ready to carry out offline learning by making some adjustments to their study habits.